Influence of peak oral temperatures on veneer-core interface stress state - Massimo Marrelli; Antonella Pujia; Davide Apicella; Salvatore Sansalone; Marco Tatullo (Taylor & Francis Group, 2015)
Objective: There is a growing interest for the use of Y-TZP zirconia as core material in veneered all-ceramic prostheses. The objective of this study was to evaluate the influence of CET on the stress distribution of a porcelain layered to zirconia core single crowns by finite elements analysis. Material and methods: CET of eight different porcelains was considered during the analysis. Results: Results of this study indicated that the mismatch in CET between the veneering porcelain and the Y-TZP zirconia core has to be minimum (0.5-1 μm/mK) so as to decrease the growing of residual stresses which could bring chipping. Conclusions: The stress state due to temperature variation should be carefully taken into consideration while studying the effect of mechanical load on zirconia core crown by FEA. The interfacial stress state can be increased by temperature variation up to 20% with respect to the relative failure parameter (interface strength in this case). This means that stress due to mechanical load combined to temperature variation-induced stress can lead porcelain veneer-zirconia core interfaces to failure.